OsRRM, an RNA-Binding Protein, Modulates Sugar Transport in Rice (Oryza sativa L.) - Liu, Derui; Xu, Lina; Wang, Wei; Jia, Shuwen; Jin, Sukui; Gao, Jiping (Frontiers in Plant Science, 2020)
Sugar allocation between vegetative and reproductive tissues is vital to plant development, and sugar transporters play fundamental roles in this process. Although several transcription factors have been identified that control their transcription levels, the way in which the expression of sugar transporter genes is controlled at the post-transcriptional level is unknown. In this study, we showed that OsRRM, an RNA binding protein, modulates sugar allocation in tissues on the source-to-sink route. The OsRRM expression pattern partly resembles that of several sugar transporter and transcription factor genes that specifically affect sugar transporter gene expression. The mRNA levels of almost all of the sugar transporter genes are severely reduced in the osrrm mutant, and this alters sugar metabolism and sugar signaling, which further affects plant height, flowering time, seed size, and starch synthesis. We further showed that OsRRM binds directly to mRNAs encoded by sugar transporter genes, and thus may stabilize their transcripts. Therefore, we have uncovered the physiological function of OsRRM, which sheds new light on sugar metabolism and sugar signaling.